Technical details of thoracic endovascular aortic repair with fenestrations for thoracic aortic pathologies involving the aortic arch: A Chinese expert consensus - Qiu, Chenyang; Li, Zhenjiang; Dai, Xiangchen; Lu, Xinwu; Lu, Qingsheng; Li, Xiaoqiang; Zhou, Weimin; Guo, Pingfan; Pan, Jun; Li, Donglin; Wu, Ziheng; Zhang, Hongkun (Frontiers in Cardiovascular Medicine, 2022)
Thoracic aortic pathologies involving the aortic arch are a great challenge for vascular surgeons. Maintaining the patency of supra-aortic branches while excluding the aortic lesion remains difficult. Thoracic EndoVascular Aortic Repair (TEVAR) with fenestrations provides a feasible and effective approach for this type of disease. The devices needed in the procedure are off-the-shelf, with promising results reported in many medical centers. Up until now, there have been no guidelines focusing exclusively on the details of the TEVAR technique with fenestrations. Experts from China have discussed the technical parts of both in situ fenestrations (needle and laser) and fenestrations in vitro (direction inversion strategy and guidewire-assisted strategy), providing a technical reference to standardize the procedure and improve its results.